Detection of differentially culturable tubercle bacteria in sputum from drug-resistant tuberculosis patients - Gordhan, Bhavna G.; Sewcharran, Astika; Letsoalo, Marothi; Chinappa, Thilgavathy; Yende-Zuma, Nonhlanhla; Padayatchi, Nesri; Naidoo, Kogieleum; Kana, Bavesh D. (Frontiers in Cellular and Infection Microbiology, 2022)
Several studies described the presence of non-replicating, drug-tolerant differentially culturable tubercle bacteria (DCTB) in sputum from patients with active tuberculosis (TB). These organisms are unable to form colonies on agar but can be recovered in liquid media supplemented with culture filtrate as a source of growth factors. Herein, we undertook to investigate the response of DCTB during the treatment of individuals with drug-resistant TB. A cohort of 100 participants diagnosed with rifampicin-resistant TB were enrolled and prospectively followed to monitor response to therapy using routine culture and limiting dilution assays, supplemented with culture filtrate (CF) to quantify DCTB. Fifteen participants were excluded due to contamination, and of the remaining 85 participants, 29, 49, and 7 were infected with rifampicin mono-resistant (RMR), multidrug-resistant (MDR), or extremely drug-resistant (XDR) TB, respectively. Analysis of baseline sputum demonstrated that CF supplementation of limiting dilution assays detected notable amounts of DCTB. Prevalence of DCTB was not influenced by smear status or mycobacterial growth indicator tube time to positivity. CF devoid of resuscitation promoting factors (Rpfs) yielded a greater amount of DCTB in sputum from participants with MDR-TB compared with those with RMR-TB. A similar effect was noted in DCTB assays without CF supplementation, suggesting that CF is dispensable for the detection of DCTB from drug-resistant strains. The HIV status of participants, and CD4 count, did not affect the amount of DCTB recovered. During treatment with second-line drug regimens, the probability of detecting DCTB from sputum specimens in liquid media with or without CF was higher compared with colony forming units, with DCTB detected up to 16 weeks post treatment. Collectively, these data point to differences in the ability of drug-resistant strains to respond to CF and Rpfs. Our findings demonstrate the possible utility of DCTB assays to diagnose and monitor treatment response for drug-resistant TB, particularly in immune compromised individuals with low CD4 counts.